BUDIDAYA SAMBILOTO DI ANTARA TEGAKAN TANAMAN TAHUNAN PADA WILAYAH PERKEBUNAN - jufri, akhmad; utami, noorwitri (Jurnal Sains dan Teknologi Indonesia, 2012)
One of alternatives to extend planted area for creat (Andrographis paniculata Ness) is the cultivation in estate areas. The problems to cultivate the plant in this area are shading and water availability. The objective of the research is to describe and evaluate the cultivation of creat between annual tree crops in the estate area. Lands were cleared and plowed to form plots with 20 m x 1.5 m ridge. The seedlings of creat were transplanted in beded soil at a distance of 40 cm and 40 cm. Plants were harvested before inflorencence. The yiled was 1.650 kg herb and It gave Rp 6182 net income per plot The shading caused by the trees around the plants decreased the content of andrographolide until 50 %.